Formulasi Jamu Sarabba Sebagai Herd Immunity Selama Pandemi Covid-19 - Wangi, Nisaul Barokati Seliro; Wajdi, Muh Barid Nizarudin (STAI Miftahul ULa Nganjuk, 2023)
During the outbreak of the covid-19 pandemic ,all societies have experienced a social and health crisis . In the midst of the health crisis affected by covid-19 pandemic, traditional medicine becomes an alternative which people can use to reduce or even break the chain of transmission and to maintain body immunity. Beside that herbal medicine is a medicine which has been used by Indonesian people for Centuries to maintain health ,The herbal medicine sarabba made of ginger, brown sugar, lemongrass, and coconut milk are useful for maintaining the body's immunity, relieve colds, warm the body and throat at this moment which covid medicine is yet to be found. People Will use the plants as an alternative medicine with various benefits. Plants that can be consumed and made into herbs for immune boosters. The mentoring approach/method used is ABCD (Asset Bassic Community Development). With regard to it,group 8 of student study service of Unisda helps the residents of Plaosan village, Babat, to hold counseling so that the People understand more about the benefits of herbal medicine by making and sharing video tutorials of making herbal medicine, hopefully the people can practice the way to prevent the transmission of covid 19 at home. Beside that, the saraba herbal medicine can be traded for the people to increase their economy which is currently declining